SELEKSI BAKTERI PENAMBAT NITROGEN DAN PENGHASIL HORMON IAA (Indole Acetic Acid) DARI RIZOSFER TANAH PERKEBUNAN KEDELAI (Glycine max L.) - Ratna Sari Tarigan; It Jamilah; Elimasni D (Saintia Biologi, 2013)
Rizosphere bacteria can be used to fix nitrogen and produce IAA (Indol Acetic Acid) as biofertilizer to support plant growth. The ability of rhizosphere bacteria can be improved using biotechnology. The aim of this study is to select the most potential nitrogen fixing and IAA producing bacteria. Nitrogen fixing and IAA producing bacteria were isolated using JNFB and Luria Bertani + L-tryptofan medium respectively. The ability of nitrogen fixing bacteria were tested by ARA method, while the ability of IAA producing bacteria were investigated by spectrophotometer technique of 535 nm. The highest IAA concentration was produced by isolate I3 which was 33.3 ppm and the highest concentration of nitrogen was yielded by isolate N3 which was 29.93 ppm. Both N3 isolate and I3 isolate potentially as biofertilizer known as PGPR (Plant Growth Promoting Rhizobacteria). Keywords: nitrogen fixing bacteria, IAA producing bacteria, PGPR